The Impact of self-organization and external regulatory controls on transformation of territorial system - V. N. Leksin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
The author proposes and substantiates the conception of efficiency of regulatory controls on the territorial systems, depending on the compliance of these controls with the systemic nature of the object of regulation. In this regard, the perception of territorial systems as environments of self-organization and objects of the regulatory controls is specified. The author defines the conditions of stable functioning of such systems, pattern of their transformation and the main types of regulatory controls, and criticizes the ideology of governmental regulatory controls on the territorial systems via support of “points of increase”, and on the situation in singleindustry towns.